Real-time observation of atomic scale rearrangement for homogenizing ruthenium single atoms on N-doped carbon for CO2 hydrogenation to formic acid - Lee, Kyung Rok; Jaleel, Ahsan; Park, Kwangho; Ahn, Sunghee; Haider, Arsalan; Lee, Ung; Jung, Kwang-Deog (Academic Press, 2026)
Ru catalysts on N-doped carbon exhibit remarkable activity for the hydrogenation of CO2 to formic acid. However, the heterogeneity of binding sites in supporting materials leads to catalyst deactivation, as Ru species on weaker binding sites (e.g., bare carbon or graphitic-N, are easily detached or agglomerated during the reaction. Here, we report that thermal treatment of the catalyst up to 400 degrees C in an N2 atmosphere substantially enhances its stability, achieving 95 % activity retention after five cycles of CO2 hydrogenation. The dynamic behavior of Ru aggregates under thermal conditions was closely monitored using in situ heating TEM analysis. The real-time TEM images revealed that Ru aggregates on weak binding sites progressively rearrange into uniformly dispersed single atoms on stronger binding sites (pyridinic-N or pyrrolic-N) with increasing temperature. Density functional theory calculations suggest that the migration of Ru atoms to strong pyridinic-N or pyrrolic-N sites is thermodynamically more favorable than migration to weaker binding sites such as graphene or graphitic-N site, or re-aggregation. This observation highlights a feasible strategy for enhancing the stability of active species on heterogeneous catalyst surfaces by promoting the homogenization of the active structure.